PARTISIPASI PETANI DALAM PROGRAM SWASEMBADA PADI, JAGUNG, DAN KEDELAI DI KOTA PADANGSIDIMPUAN - Kansrini, Yuliana (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2016)
The Ministry of Agriculture have enacted a special effort to escalate rice, corn and soybean productions since 2015 through the program of Rice, Corn and Soybean Self-Sufficiency. The manifestation of this program is facilitated through various activities including: tertiary irrigation improvement, land optimal, pre/post-harvest agricultural machinery aids, seed and fertilizer aids, integrated crop management movement, planting season arrangement using KATAM, and integrated escort and assistance by extension officers, universities (students) and the Army (BABINSA). The Program implementation requires farmers participation in several activities. Farmers participation indicator in this program can be observed through their involvement in four implementation stages: preparation, management, observation, and utilization. Research showed that the Program implementation in Padangsidimpuan was successful, indicated by the realization of planting area target of RJIT and OPLA programs at 100%. The farmers participation level in this Program scored 24.10 or 80.33%, the influencing factors related to the high level of participation were the farmers training quantity, their status in terms of land ownership, and assistance by extension officers and students. Problems in the Program implementation includes the limited number of extensions officers, the famers knowledge varied in technology implementation, and coordination among the related institutions was not optimum.